The Effectiveness of Role-Play-Based Storytelling Intervention in Enhancing Self-Esteem Among Elementary School Children - Frinska Daisy Leries; Bella Pratiwi; Yogi Surani; Farah Aulia (Da'wa Faculty of Islamic State University Salatiga, 2025)
Self-esteem plays a crucial role in the socio-emotional development of elementary school children. However, psychoeducational interventions that integrate storytelling and role-play remain limited and underexplored. This study aims to evaluate the effectiveness of a role-play-based storytelling intervention in improving self-esteem among elementary school students. Using a quasi-experimental one-group pretest–posttest design, 30 children participated in six sessions of a structured intervention combining narrative-based reflection and character enactment. Self-esteem was measured using the adapted Rosenberg Self-Esteem Scale, which had undergone prior construct validation. Descriptive statistics showed an increase in mean scores from pretest to posttest. Normality assumptions were re-evaluated, and paired-sample statistical testing was applied appropriately. The results indicate a significant improvement in children’s self-esteem following the intervention. The discussion integrates theoretical perspectives from positive psychology and experiential learning while acknowledging methodological limitations, including the absence of a control group and potential measurement constraints. This study highlights the potential of combining storytelling and role-play as an engaging, developmentally appropriate psychoeducational method. Future research should explore controlled experimental designs and cultural validation to strengthen generalizability.